Notes On a Metaphysics of Ens and the Actus Essendi According To Étienne Gilson - Pérez de Catalán, Patricia Carolina (Scripta Mediaevalia, 2025)
This article explores the metaphysical principles of Thomas Aquinas as understood by Gilson. When man encounters a concrete existent in sensible experience, the intellect conceives being and essence in an evident manner. However, to avoid errors in understanding reality and to clarify difficulties, it is necessary to elucidate the meaning of key terms and their relationship with logical intentions. This article examines the implications of Gilson's interpretation of Aquinas' metaphysics and its significance for understanding reality.